SIMULATION OF MECHANICAL SYSTEM STABILIZATION WITH ACTIVE RESONANCE CONTROLLER - Slavko, Olena (International Journal of Computing, 2010)
A simulation model of a mechanical system with a control algorithm based on the active resonance control approach is created. Methodology and virtual laboratory for researches of the simulation models of mechanical systems stabilization based on the active resonance control algorithm are developed. This virtual laboratory allows to research quality and stability of the active resonance algorithm for different types of mechanical systems and external disturbances for various initial conditions and environment parameters. The active resonance control algorithm for the first time is adapted and improved by using of numerical values of velocity and acceleration of a controlled object on each step of a simulation for a system described by a second order differential equation.